Application of Ethical Values Deriving from Hadiths in Creating a Conducive Learning Environment - Rahman Rahman; Hardivizon Hardivizon; Ilyas Ilyas; Zailani Zailani; Ali Akbar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to explore applying ethical values derived from the hadiths of Prophet Muhammad SAW in creating a conducive learning environment at Madrasah Aliyah Negeri (MAN) 1 Payakumbuh, West Sumatera. The research employs a qualitative approach using Hassan Hanafi's hermeneutical framework, which involves historical, eidetic, and practical criticism of hadiths related to teacher-student ethics. Data was collected through document analysis of hadiths and semi-structured interviews with teachers and students. The results indicate that applying ethical principles from the hadiths, such as respect, justice, patience, and compassion, is crucial in fostering positive interactions between teachers and students. Teachers at MAN 1 Payakumbuh have adapted their teaching methods to ensure effective understanding, including using simple language, providing feedback, and accommodating different student needs. The conclusion of this research emphasizes that implementing ethical values from the hadiths of Prophet Muhammad SAW can create a learning environment that supports students' academic and moral development. This study fills a gap in the existing literature by offering practical insights into integrating hadith-based ethics into everyday educational practices in Islamic schools, particularly in Indonesia.